Implementing the Wafa Five-Stage (5P) Right-Brain Method in Qur’an Memorization at an Indonesian Primary School: A Qualitative Case Study of Pedagogical Adaptation - Choirul Azimin; Sriani; Wiwin Narti; Andryadi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
Conventional Qur’an memorization (tahfidz) in Indonesian elementary schools often relies on uniform repetition that disregards the concrete-operational cognition of children aged 7–12, yielding fatigue, motivational decline, and uneven progress. The Wafa method, structured around a five-stage protocol (Opening, Experiencing, Teaching, Assessing, Closing abbreviated 5P) and grounded in right-brain multisensory learning, has been promoted as a pedagogical response, yet most existing studies report aggregate effectiveness without examining how classroom teachers operationalize and adapt it when contextual constraints emerge. This study therefore investigates the planning, enactment, encountered constraints, and adaptive strategies of the Wafa 5P method at SD Lab School Integrated SKB, Bungo Regency, Indonesia. A qualitative case-study design was employed; data were generated over a ten-week period (March–May 2024) through participant observation of 24 lessons, semi-structured interviews with eight purposively sampled informants (principal, four tahfidz teachers, three homeroom teachers), and document analysis. Analysis followed the Miles, Huberman, and Saldaña interactive model, with credibility secured through source and method triangulation and prolonged engagement. Findings show that the 5P protocol was implemented in full sequence but encountered three recurrent constraints: difficulty internalizing the Hijaz tonal pattern, irregular attendance linked to home distance, and heterogeneous memorization pace within a 35-minute slot shared with Dhuha prayer. Teachers responded with three contextual adaptations: routine playback of child-oriented murottal audio, autonomy-supportive responses to tardiness coupled with catch-up tasks, and a 14:30–17:00 supplementary tahfidz class. Findings reframe Wafa as a teacher-mediated, context-responsive system, contributing evidence for differentiated Qur’an instruction in primary education.